Central America Social Expenditures and Institutional Review : Honduras - World Bank (Washington, DC, 2015)
Honduras has experienced moderate economic growth in the past decade, in line with the rest of the region. Despite this growth track record, limited opportunities for decent jobs for the majority of workers have resulted in stagnant poverty and inequality rates that are still the highest in Central America (CA). In parallel, progress in human development indicators has also been mixed in the last decade. In education, while primary enrollment has significantly increased, low coverage at all other levels of education, inequalities in access and low quality persist. In health, Honduras is close to achieving the 2015 child mortality Millennium Development Goals (MDGs), but maternal mortality, noncommunicable diseases (NCDs), and violence pose additional challenges. And despite advances in setting up a social protection system, fiscal sustainability and lack of coordination among interventions prevail, undermining poverty reduction efforts. The ability of the Honduras government to expand safety nets, to increase the access and quality of public education and health services, to engage in active labor market policies, and to improve human development indicators in general, remains limited for a number of reasons. First, overall real social public spending has been on the decline in the last few years. Second, low revenues and fiscal deterioration pose challenges to adequately financing needed social sector improvements. Third, challenges in budget formulation and execution (mainly due to institutional factors) also diminish the impact of social spending. But more importantly, Honduras needs to significantly improve the effectiveness and efficiency of its social spending. This note argues that moving forward Honduras should prioritize three main aspects: a) to rationalize and increase the effectiveness of social public spending by enhancing the pro-poor features of targeting mechanisms; b) to significantly redress the imbalance between recurrent spending, especially the wage bill, and capital expenditure; and c) to continue strengthening information systems tools, legislation, and institutions in an effort to consolidate programs into fewer and higher impact interventions. Sector-specific challenges aligned with these broad objectives are addressed below.